Water polo throwing speed and body composition: an analysis by playing positions and opposition level - Fiol, C. F.; Abraldes, J. A.; Manchado, C.; Vila, H. (Journal of Human Sport & Exercise, 2015)
The aim of this study was to develop an anthropometric profile on highly skilled male water polo players by specific playing positions. Also, to identify significant relationships between these features an overhead throwing speed in highly skilled male Water Polo players by specific playing positions. Methods: A total of 94 male water polo players (24.5±5.3 yrs) who were playing in the Spanish King´s cup were studied. Subjects were grouped according to their specific playing positions: 15 goalkeepers, 45 offensive wings, 20 center backs and 14 center forwards. Anthropometric assessment was made following ISAK protocols. Hand grip and throwing speed in several situations were also assessed. A one-way analysis of variance (ANOVA) was used to determine if significant differences existed among the four playing positions. Pearson product-moment correlation coefficients (r) were used to determine the relationships of all anthropometric measures with throwing speed and hand grip. The total player`s somatotype was endomorphic-mesomorphic (2.9-5.8-2.3). Center forwards exhibit important anthropometric differences compared with the other specific playing positions in elite male water polo players, but no differences were found in throwing speed by specific playing positions in each throwing conditions. Moreover, a higher number of relationships between anthropometric and throwing speed were found in wings and also in center backs but no relationships were found in center forwards. The data reflects the importance of muscle mass and upper body in the throwing skill. Coaches can use this information in order to select players for the different specific positions.